Bridging ties: a source of firm heterogeneity in competitive capabilities - McEvily, Bill; Zaheer, Akbar (Strategic Management Journal, 1999)
What explains differences in firms’ abilities to acquire competitive capabilities? In this paper we propose that a firm’s embeddedness in a network of ties is an important source of variation in the acquisition of competitive capabilities. We argue that firms in geographical clusters that maintain networks rich in bridging ties and sustain ties to regional institutions are well-positioned to access new information, ideas, and opportunities. Hypotheses based on these ideas were tested on a stratified random sample of 227 job shop manufacturers located in the Midwest United States. Data were gathered using a mailed questionnaire. Results from structural equation modeling broadly support the embeddedness hypotheses and suggest a number of insights about the link between firms’ networks and the acquisition of competitive capabilities. Copyright © 1999 John Wiley & Sons, Ltd.